On the correspondence between gravity fields and CFT operators - FROLOV, SERGEY (My University, 2000)
It is shown that a nonlinear derivative-dependent transformation of gravity fields changes correlation functions in a boundary CFT, and, therefore, corresponds to a change of a basis of operators in the CFT. It is argued that only non-renormalized structures in correlation functions can be changed by such a field transformation, and that the study of the response of correlation functions to gravity field transformations allows one to find them. In the case of 4-point functions of CPOs in SYM4 several non-renormalized structures are found, including the extremal and subextremal ones. It is also checked that quartic couplings of scalar fields sI that are dual to extended chiral primary operators vanish in the subextremal case, as dictated by the non-renormalization theorem for the subextremal 4-point functions and the AdS/CFT correspondence.
PUBLISHED
Keywords: Particles and fields physics; superstring theory; supergravity models